Chondrogenic Differentiation Capacity of Human Umbilical Cord Mesenchymal Stem Cells with Platelet Rich Fibrin Scaffold in Cartilage Regeneration (In Vitro Study) - Sumarta, Ni Putu Mira; D, Coen Pramono; Hendrianto, Eryk; Susilowati, Helen; Karsari, Deya; Rantam, Fedik A. (BALI MEDICAL JOURNAL, 2016)
Background: Human umbilical cord mesenchymal stem cell is a promising source of allogenous MSC with great chondrogenic differentiation capacity. Meanwhile, platelet rich fibrin (PRF) is a natural fibrin matrix, rich in growth factors, forming a smooth and flexible fibrin network, supporting cytokines and cell migration, thus can be used as a scaffold that facilitate the differentiation of MSC. However, the differential capability of MSC cultured in PRF was still poorly understood. Method: We studied in vitro differentiation potential of MSC cultured in PRF by evaluating several markers such as FGF 18, Sox 9, type II collagen, aggrecan in 3 different culture medium. Result: The result showed that there was positive expression of FGF 18, Sox 9, type II collagen, aggrecan in all medium of in vitro culture. Conclusion: MSC cultured from human umbilical cord had the capacity of chondrogenic differentiation and able to produce cartilage extracellular matrix in vitro which means that hUCMSC is a potential allogeneic MSC for cartilage regeneration.
Keywords: umbilical cord, mesenchymal stem cell, chondrogenic medium.